Pelaksanaan Evaluasi Pembelajaran Berbasis Higher Order Thinking Skills (HOTS) - Wahidin, Wahidin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
Curriculum developments continue to be made in the world of education, especially in the assessment system. The curriculum currently being implemented in Indonesia is the 2013 curriculum, better known as K13. In K13, the evaluation applied is based on HOTS (High Order Thinking Skills). The implementation of HOTS-based evaluation in learning aims to ensure that learning outcomes can motivate students to develop their thinking abilities so that they can think creatively and innovatively. This article discusses it conceptually with the aim of providing knowledge about the concepts, characteristics, and steps in preparing HOTS-based assessments, especially for educators. The steps for preparing a HOTS-based evaluation are: (1) analyzing the basic competencies that will be made in a HOTS-based assessment; (2) compiling an assessment grid that is in accordance with the basic competencies that have been analyzed; (3) linking them to interesting problems in daily life; (4) writing it in the form of questions; and (5) creating scoring and assessment guidelines and answer keys.